FIGURATIVE LANGUAGE IN ENGLISH STAND-UP COMEDY - Maharani Widya Putri; Erwin Oktoma; Roni Nursyamsu (University of Kuningan, 2016)
This descriptive qualitative research was about the analysis of figurative language in English stand-up comedy. The purposes of this study were to identify the types of figurative language and to describe the functions of figurative language found in the selected video of stand-up comedy show. The data source was taken from one of selected videos of Russell Peters stand-up comedy show. Russell Petersâ€™s speech contained about figurative language in the video is observed. The data were collected through content analysis technique by collecting the verbal language used by Russell Peters. The first research questions was analyzed by McArthur (1992) theory and supported by Crystal (1994) theory to find out the types of figurative language found in English stand-up comedy. To answer the second research questions about the functions of figurative language found in English stand-up comedy was analyzed by Chunqi (2014) theory and suppoted by Kokemuller (2001) theory and Turner (2016) theory. After analyzing data, it was found that Irony was the most dominant figurative language used by Russell Peters in â€œRussell Peters Comedy Now! Uncensoredâ€ with 29.94%. It was happened because the kind of topics used by Russell Peters in that show were about ethnics (canadian, white people, black people, brown people and asian), society case (beating child) and culture (accent and life style of various ethnics in the world, habitual of various ethnics in the world). Irony and Hyperbole were needed dominantly in the performance, to entertain the audiences in the stand-up comedy show. The function of eleven types of figurative language which were used by Russell were concluded. The functions were to amuse people in comedic situations, to expand meaning, to explain abstract emotions, to make sentence interesting represented and give creative additions. Keywords: Figurative Language, Stand-Up Comedy, English Stand-Up Comedy